Investigations into fault ride through and fault location for HVDC - Noori, Abdulrazzaq Fouad Noori (2019)
Voltage Source Converter - High Voltage Direct Current (VSC-HVDC) transmission systems have been rapidly developed and received great interest in off-shore wind power applications, because of the increase in the energy demand, compact size and ability to connect asynchronous AC systems. Multi-Terminal Direct Current (MTDC) networks have great potential to support AC transmission networks. Therefore DC networks have to be reliable and vulnerable to faults. Modular Multilevel converters (MMCs) have high power quality and capability. In this thesis a new control approach is proposed for the MMC in order to ride through an AC, DC faults and unbalanced conditions. The performance of this converter is tested under three scenarios; AC single line to ground (SLG) fault, Island operation, and grid connected operation. A three-terminal VSC-HVDC system is simulated in Matlab/Plecs, which consists of MMC at each terminal and HVDC line presented as π-model. Master-slave power flow control and fault detection method are considered to conduct the protection study during DC pole to ground fault. This thesis presents a new strategy to estimate the location of faults in an HVDC submarine cable based on impedance estimation. A simplified two terminal system is considered with a modular multilevel converter (MMC) on one of the terminals of a fault and an ideal current source on the other one. Three different ways have been considered for representing the cable impedance. The first is the conventional cascaded pi model; the second is using the resonance frequency equation and the third is using the Frequency Dependent Model (FDM). The transient caused as the MMC reacts to a fault MMC is used to identify the fault location based on the resonance frequency of cable impedance. The proposed method gives good results for different DC pole to ground fault locations with an acceptable error. Experimental work is done to demonstrate and validate the proposed control and the fault location strategy. The control structure of the experimental MMC is tested under unbalance AC load and compared with the conventional vector control. The prototype is supplied by a DC voltage through a cable represented by three π models where the pole to ground fault is placed with a three phase RL load on the AC side.